Given that the line passes through two points
(-2,-2) and (x1,y1)
Equation in point slope form is
y-y1 = m(x-x1)
substitute for slope
Hence equation of the line =
![(y2-y1)/(x2-x1) =[tex]y-y1 = (-2-y1)/(-2-x1)(x-x1)](https://img.qammunity.org/2019/formulas/mathematics/high-school/idp2n113b7ynrv6i9mloh778im2o0nv3y4.png)
Since we donot know the value of x1or y1 the equation would contain x1, y1 also as answer.
Answer in point slope form is
![(y2-y1)/(x2-x1) =[tex]y-y1 = (-2-y1)/(-2-x1)(x-x1)](https://img.qammunity.org/2019/formulas/mathematics/high-school/idp2n113b7ynrv6i9mloh778im2o0nv3y4.png)